1994
DOI: 10.1046/j.1537-2995.1994.341195065031.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of symptomatic bacteremia following platelet transfusion and of its management

Abstract: Significant febrile reactions after platelet transfusion are highly likely to be indicative of bacteremia. Routine retention of platelet bags for subsequent microbiologic study was useful in the investigation of these febrile reactions. Empiric antibiotic therapy is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(67 citation statements)
references
References 30 publications
4
63
0
Order By: Relevance
“…Ironically, the majority (85%) of platelets are transfused to patients in the medical oncology, hematology, pediatric hematology/oncology, and bone marrow transplantation settings, all typically immunosuppressed patients (61). A study of platelet transfusions in autologous bone marrow transplant patients found that 1 in 2,000 units of platelet concentrates associated with a febrile episode (within 24 h of transfusion) were linked to bacterially contaminated platelets (16). Of the 10 patients known to have received a bacterially contaminated unit, 4 experienced septic shock.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Ironically, the majority (85%) of platelets are transfused to patients in the medical oncology, hematology, pediatric hematology/oncology, and bone marrow transplantation settings, all typically immunosuppressed patients (61). A study of platelet transfusions in autologous bone marrow transplant patients found that 1 in 2,000 units of platelet concentrates associated with a febrile episode (within 24 h of transfusion) were linked to bacterially contaminated platelets (16). Of the 10 patients known to have received a bacterially contaminated unit, 4 experienced septic shock.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Episodes of bacteraemia as a result of platelet transfusion were excluded from the study. 6 All isolates in polymicrobial bacteraemia, multiple episodes of bacteraemia and break-through bacterae-mia were included, but any patient with multiple isolates was counted only once in the statistical analysis for risk factors predisposing to bacteraemia.…”
Section: Patients and Antimicrobial Prophylaxismentioning
confidence: 99%
“…Although temporarily effective in controlling severe thrombocytopenia, platelet transfusion therapy is associated with several problems, including refractoriness and alloimmunization, transmission of infectious agents, and transfusion reactions. [9][10][11][12][13][14][15] The limited supply of blood products can also be problematic. The use of doseintensive chemotherapy regimens and hematopoietic progenitor cell transplantation, as well as intensive support for the medical and surgical patient, has resulted in an increasing demand for platelet products; this demand is likely to escalate in an attempt to improve clinical outcomes for oncology and nononcology patients.…”
Section: Introductionmentioning
confidence: 99%